Contribution, Utilization, and Improvement of Legumes-Driven Biological Nitrogen Fixation in Agricultural Systems - Kebede, Erana (Frontiers in Sustainable Food Systems, 2021)
Legumes improve soil fertility through the symbiotic association with microorganisms such as rhizobia which fix the atmospheric nitrogen and make nitrogen available to the host and other crops by a process known as biological nitrogen fixation (BNF). Legumes included in the cropping system improve the fertility of the soil and the yield of crops. The advantages of legumes in the cropping system are explained in terms of direct nitrogen transfer, residual fixed nitrogen, nutrient uptake, effect on soil properties, breaking of pests’ cycles, and enhancement of other soil microbial activity. The best benefit from the legume and BNF system can be utilized by integrating legumes into cropping systems. The most common practices to integrate the BNF into agricultural systems are crop rotation, simultaneous intercropping, improved fallows, green manuring, and alley cropping. However, the level of utilizing nitrogen fixation requires the improvement of the systems by selecting legume genotypes, inoculating with effective rhizobia, and use of appropriate agronomic practices and cropping systems. Therefore, using legumes at their maximum genetic potential, utilization of BNF from legumes, and inoculation of legumes with compatible rhizobia are very important for increasing food production to accommodate the increasing world population. Priority should, thus, be given to value the process of BNF through more sustainable technologies and expansion of knowledge to the system.